Influence of pro-angiogenic cytokines on proliferative activity and survival of endothelial cells - Garmanchouk, L.V.; Pyaskovskaya, O.N.; Solyanik, G.I. (Вiopolymers and Cell, 2010)
Tumor angiogenesis in contrast to physiological one is characterized by high level of malignant cell production of proangiogenic cytokines, which have different influence on functional activity of endothelial cells. The aim of the study – to carry out a comparative analysis of the influence of a vascular endothelial growth factor (VEGF) and an epidermal growth factor (EGF) on proliferative activity and survival of endothelial cells upon their confluent and exponential growth. Methods. The proliferative activity of endothelial cells was determined by MTT-test and their viability was detected by the trypane blue exclusion test. Results. It was shown that EGF (irrespectively of the level of serum factors) in concentrations higher than 10 ng/ml activated the proliferative activity of confluent endotheliocytes in a concentration-dependent manner by 18–36 % (p < 0.05) as compared to the control, while this cytokine did not affect the endothelial cells in the exponential growth phase. VEGF in wide concentration range did not display the mitogenic effect on endotheliocytes in both confluent and exponential growth phases. Furthermore, VEGF in concentrations higher than 100 ng/ml inhibited proliferative activity of confluent endothelial cells by 12 % (p < 0.05). In case of deficiency of nutrients, EGF and VEGF promoted the survival of endothelial cells, considerably decreasing their death. Conclusions. EGF, in contrast to VEGF, stimulates proliferation and survival of the endothelial cells, whereas VEGF has significant influence only on the survival of the cells.